Study of Some Anti-tubercular Agents - N. Modi, Ashvin; Naik, Bhadresh; Desai, Pratibha; Desai, C.M.; Patel, Dinesh (Asian Journal of Chemistry, 2010)
The anti-TB activity of some benzylidene derivatives of sulfa-thiazoleand sulfa-phenazole against H37Rv is inhibitory at 5 μ/mL,while that for pyridine derivatives is nil.